Upregulation of Helicoverpa armigera core RNA interference genes by bacterial infections and its effect on the insect–bacteria interaction. Issue 2 (20th December 2018) - Baradaran, E.; Moharramipour, S.; Asgari, S.; Mehrabadi, M.
Abstract: RNA interference (RNAi) is an extremely conserved defence mechanism. The antiviral role of the RNAi pathway in insects is well documented; however, the relevance of this pathway in other aspects of insect immunity is largely unknown. In this study, we questioned whether RNAi has any function during insect–bacteria interactions. For this, we assessed induction of the RNAi pathway in response to bacterial infections by monitoring the expression of dicer1 / argonaute1 and dicer2 / argonaute2, which are important genes in the microRNA and short interfering RNA sub‐pathways respectively. Bacterial cells of Bacillus thuringiensis and Serratia marcescens were injected into the haemocoel of fifth‐instar larvae of Helicoverpa armigera, whereas double‐distilled water was injected into control insects. Expression levels of the RNAi‐related genes increased in the bacteria‐injected larvae compared with controls. Transcript knockdown of dicer1 reduced the replication of B. thuringiensis ; as a consequence, larval mortality decreased compared with the control. However, replication of S. marcescens increased following dicer1 silencing, which led to higher rates of larval mortality when compared with the control. RNAi of dicer2 promoted replication of both bacteria in the larvae and also enhanced larval mortality. Therefore, dicer1 and dicer2 affected larval survival and the replication rates of the pathogenic bacteria, suggesting their roles in the interactions.